Factors Influencing the Choice of Automated Peritoneal Dialysis Treatment by Patients Receiving Home Peritoneal Dialysis - Cao F; Hong F; Ruan Y; Lin M (Patient Preference and Adherence, 2023)
Fang Cao,1,2 Fuyuan Hong,1 Yiping Ruan,1 Miao Lin1 1Department of Nephrology, Provincial Clinical College, Fujian Medical University, Fujian Provincial Hospital, Fuzhou, 350001, People’s Republic of China; 2Department of Nursing, Provincial Clinical College, Fujian Medical University, Fujian Provincial Hospital, Fuzhou, Fujian, 350001, People’s Republic of ChinaCorrespondence: Fang Cao; Miao Lin, Department of Nephrology, Provincial Clinical College, Fujian Medical University, Fujian Provincial Hospital, 134 East Street, Fuzhou, 350001, People’s Republic of China, Tel +86-591-87557768, Email 422512642@qq.com; 10151246@qq.comObjective: This study was conducted to understand the influencing factors for home peritoneal dialysis patients choosing APD and to provide a scientific basis for improving the completion rate of APD treatment and the follow-up of peritoneal dialysis patients.Methods: The study was a cross-sectional questionnaire-based study. A total of 588 patients on peritoneal dialysis were randomly selected from 6 regions in Fujian Province in southern China using a stratified cluster sampling method.Results: The mean age of the patients were 56.5 ± 14.73 years. In the univariate analysis, knowledge, user experience and family support were the factors that affected patients’ choice of APD (all P < 0.05) and were positively correlated with the treatment utilization rate. In the multivariate analysis, 3 factors (treatment with APD, knowledge of APD, and family support) remained significantly associated not choosing APD. The selection rate for APD was 2.594 times higher among patients who had received APD than among patients who had never received APD. The selection rate for patients with “a lot of knowledge” about APD was 10.75 times that of patients with “no knowledge”.Conclusion: Patients’ knowledge of APD, experience in application and family support were the main factors affecting the choice of APD as a treatment mode (P < 0.05) and were positively correlated with the treatment utilization rate. Further studies are needed to improve the APD treatment completion rates by modulation the above-mentioned factors.Relevance to Clinical Practice: This study provides scientific evidence for improving APD treatment completion rates and improving patient quality of life.Keywords: peritoneal dialysis, APD, dialysis mode, influencing factors, follow up, end-stage kidney disease